2005
DOI: 10.1002/bip.20215
|View full text |Cite
|
Sign up to set email alerts
|

Potential of NIR‐FT‐Raman spectroscopy in natural carotenoid analysis

Abstract: This paper demonstrates the special advantages of FT-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
214
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(221 citation statements)
references
References 43 publications
4
214
0
3
Order By: Relevance
“…The RR spectra (Fig. 8) are very similar to those reported previously (14,38). However, as the C-H out-of-plane wagging vibrations have been considered to be an important reporter of zeaxanthin binding to PsbS (14,15), a curve-fitting analysis of the 930 -990 cm Ϫ1 frequency region has been carried out (Fig.…”
Section: Wt E122q E226q Npq4supporting
confidence: 78%
“…The RR spectra (Fig. 8) are very similar to those reported previously (14,38). However, as the C-H out-of-plane wagging vibrations have been considered to be an important reporter of zeaxanthin binding to PsbS (14,15), a curve-fitting analysis of the 930 -990 cm Ϫ1 frequency region has been carried out (Fig.…”
Section: Wt E122q E226q Npq4supporting
confidence: 78%
“…6c) confirmed that the pigments are indeed carotenoids (although the peaks are hypsochromically shifted as a result of solvation), as previously investigated in detail (see, e.g. Strain, 1938; Zang et al ., 1997; Maoka et al ., 2000; Withnall et al ., 2003; Schulz et al ., 2005; Barrell et al ., 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows averaged Raman spectra for P. aeruginosa biofilm. It is characterized by vibrational bands typical for nucleic acids, proteins, lipids, carbohydrates and carotenoids (see Table 1) [19, [39][40][41][42]. The prominent Raman bands of biofilm belong to proteins: 1002 cm −1 (phenylalanine), 1243 cm −1 (amide III) and 1658 cm −1 (amide I).…”
Section: Resultsmentioning
confidence: 99%